Activated carbon fiber composite manganese-based catalyst for catalytic combustion of VOCs as well as preparation method and application of activated carbon fiber composite manganese-based catalyst
The preparation of activated carbon fiber composite manganese-based catalysts through ball milling, mixing and extrusion molding technology has solved the problem of poor effect of existing catalysts in degrading low-concentration VOCs, and achieved a lower cost and more efficient VOCs catalytic combustion effect. Industrial production demand.
Patent Information
- Application Number
- CN202411483153.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing VOCs catalytic combustion catalysts are not effective in degrading low-concentration VOCs, and have high preparation costs and low utilization of active components, making it difficult to adapt to industrial production needs.
The activated carbon fiber composite manganese-based catalyst is prepared by ball milling, mixing and extrusion molding technology, and the adsorption capacity and catalytic activity of the catalyst are improved by adding activated carbon fibers.
It effectively reduces the cost of preparing raw materials, improves the capture ability of low-concentration VOCs, and realizes the complete catalytic combustion of VOCs at lower temperatures, making it suitable for large-scale industrial use.
Smart Images

Figure CN119488899A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to an activated carbon fiber composite manganese-based catalyst for catalytic combustion of VOCs, a preparation method and an application thereof. Background Art
[0002] At present, the VOCs treatment technologies generally used at home and abroad include: adsorption / absorption method, condensation method, membrane separation method, photocatalytic method, direct combustion method and catalytic combustion method. Among them, the catalytic combustion method is an economical VOCs treatment method. It is a new treatment method with low energy consumption, low emissions, green environmental protection and no secondary pollution. Commonly used catalysts are generally divided into two categories: precious metal supported catalysts and transition metal oxide catalysts. Precious metal catalysts mainly use Pt, Pd, Rh, Au, Ru and the like as active components, and activated carbon, molecular sieves, rare earth composite oxides, inactive high specific surface area oxides and the like as carriers to improve dispersibility and anti-poisoning ability. They generally have excellent low-temperature catalytic performance, but the cost is high, the raw materials are scarce and they are easy to sinter. Transition metal oxide catalysts mainly use oxides of transition metals such as Mn, Fe, Co, Cu, Ni, and Ce as active components. They are used directly or loaded on carriers with large specific surface areas such as activated carbon, Al2O3, and TiO2. The catalytic activity is effectively improved by utilizing the variable valence states of transition metals and the synergistic effect of metal oxides after mutual doping. Different doping combinations can also be adopted for different types of VOCs.
[0003] In the related art, the preparation methods of VOCs treatment catalysts mainly include coprecipitation method, template method, citric acid complexation method, etc., and also include some supported and integral catalyst preparation methods. Invention application patent 202310157637.0 discloses a Mn-Ce catalyst for catalytic combustion of VOCs exhaust gas. The patent uses manganese-based metal salts supplemented with other metal salts as modifiers as precursors, citric acid as a complex, and is obtained by calcination of metal salts by thermal decomposition. When the molar ratio of Mn to Ce is 4:1, the catalyst can degrade 90% of toluene or ethyl acetate below 200°C. Invention application patent 202210404645.6 discloses a method for preparing a catalyst for catalytic combustion of VOCs, and the steps are as follows: dissolve the metal oxide, centrifuge, wash, dry, and roast to obtain a metal oxide as a carrier, and then mix the precious metal solution with the metal oxide carrier, wash, dry, and roast to obtain a precious metal catalyst with rare earth metal oxide-metal oxide as a carrier. This catalyst can effectively degrade benzene between 200 and 260°C. Although the catalysts prepared by these preparation methods have excellent performance, they have high preparation costs, low utilization rates of active components, and poor degradation effects on some very low concentration VOCs. Therefore, how to prepare a catalyst suitable for low concentration VOCs degradation and industrial production is a problem that needs to be solved at present. Summary of the invention
[0004] To solve the above problems, the present invention provides a method for preparing an activated carbon fiber composite manganese-based catalyst for catalytic combustion of VOCs. This method adopts ball milling, mixing, and extrusion molding technology to prepare a catalyst with a certain fixed form, which effectively increases the utilization rate of active components. The addition of activated carbon fibers can effectively enhance the capture of VOCs by the catalyst, and is suitable for VOCs catalytic oxidation catalysts used under industrial conditions.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing an activated carbon fiber composite manganese-based catalyst for catalytic combustion of VOCs, the method comprising the following steps:
[0007] (1) adding a precipitant to a metal salt solution for precipitation, and then aging, filtering, washing and drying in sequence to obtain a metal hydroxide precursor;
[0008] (2) adding a metal hydroxide precursor, a solid forming agent, an extrusion agent and activated carbon fibers into a ball mill, grinding and mixing them uniformly; after mixing, adding acid to make the raw materials bond into a mass and age;
[0009] (3) extruding and aging the material after aging in step (2) again;
[0010] (4) Drying the aged material in step (3), and then calcining it to obtain a composite manganese-based catalyst.
[0011] In the above preparation method: in step (1), the metal composition in the metal salt is copper-manganese with a molar ratio of 1-3:1-3 or iron-manganese with a molar ratio of 1-3:1-3 or cerium-manganese with a molar ratio of 1-3:1-3.
[0012] In the above preparation method: in step (1), the precipitant is one of a sodium hydroxide solution or a potassium hydroxide solution, the concentration of the precipitant is 1 to 4 mol / L, and the precipitation condition is a pH value of 10 to 12.
[0013] In the above preparation method: in step (1), the drying temperature is 60-120° C. and the drying time is 12 to 24 hours.
[0014] In the above preparation method: in step (2), the solid forming agent is one of pseudo-boehmite or alumina, and the extrusion agent is one of sesbania gum or talc.
[0015] In the above preparation method: in step (2), the mass ratio of the solid forming agent to the metal hydroxide precursor is 3-7:3-10; the mass of the extrusion agent added is 2-5% of the total mass of the solid forming agent and the metal hydroxide precursor; the amount of activated carbon fiber added is 1% to 5% of the total mass of the solid forming agent and the metal hydroxide precursor.
[0016] In the above preparation method: in step (2), the acid added is a nitric acid solution with a volume fraction of 2.5-15%; the volume ratio of the raw material to the acid after ball milling is 1:1-1.7:1.
[0017] In the above preparation method: in steps (1) to (3), the aging temperature is room temperature and the aging time is 24 to 48 hours.
[0018] Preferably, in step (4), the drying temperature is 100-140° C., and the drying time is 20-24 hours; the calcination temperature is 450-550° C., and the calcination time is 3-6 hours.
[0019] An activated carbon fiber composite manganese-based catalyst for catalytic combustion of VOCs is prepared by the above method.
[0020] In the technical solution of the present invention, the catalyst prepared by the above method is used in the catalytic combustion of VOCs.
[0021] The concept of the present invention is as follows:
[0022] This application is in view of the large amount of domestic industrial waste gas, strong volatility, and difficulty in post-treatment, the lack of effective treatment for some low-concentration VOCs, and the fact that many catalyst preparation methods are not suitable for large-scale industrial production. The present invention creatively provides a method for preparing an activated carbon fiber composite manganese-based catalyst for catalytic combustion of VOCs. This method adopts ball milling, mixing, and extrusion molding technology to prepare a catalyst with a certain fixed form. The use of extrusion molding technology can effectively increase the utilization rate of active components, and at the same time, the catalyst ratio can be changed to cope with different catalytic scenarios. Among them, the addition of activated carbon fibers can effectively enhance the capture of VOCs by the catalyst, combining adsorption-catalysis technology, which is suitable for effective capture and adsorption of some volatile and low-concentration VOCs under industrial conditions, and further catalytic degradation, reducing the harm of VOCs to the environment and human body.
[0023] The present invention has the following beneficial effects:
[0024] 1. The preparation method of the present application can effectively reduce the cost of raw materials and is suitable for large-scale industrial use.
[0025] 2. A certain amount of activated carbon fiber is added in the preparation method of the present application to enhance the adsorption effect, which can effectively improve the capture capacity of low-concentration VOCs in the environment and achieve complete catalytic combustion of VOCs at a lower temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The degradation effect of different VOCs in Example 1; the air velocity condition is 6000h -1 ; VOCs concentration is 1000ppm.
[0027] Figure 2 The catalytic degradation effect of ethyl acetate before and after adding 5% activated carbon fiber; the space velocity condition is 15000h -1 ; Ethyl acetate concentration is 1000ppm.
[0028] Figure 3 Comparison of the catalytic degradation of ethyl acetate by a common coprecipitation catalyst and the catalyst prepared by this patent; the space velocity condition is 15000h -1 ; Ethyl acetate concentration is 1000ppm. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto:
[0030] Embodiment 1:
[0031] (1) Ce(NO3)3 and Mn(NO3)2 metal salts were dissolved in water at a metal element molar ratio of 1:2, 1 mol / L NaOH solution was added to the solution as a precipitant, and the solution was stirred until the pH value was 12; after 24 hours of standing aging at room temperature, the solution was filtered, washed, and dried at 100°C for 12 hours to obtain a CuMn metal hydroxide precursor.
[0032] (2) Add the CuMn metal oxide precursor and pseudo-boehmite into a ball mill at a mass ratio of 5:5, and add 2%wt sesbania gum (the amount added is relative to the total mass of the CuMn metal oxide precursor and pseudo-boehmite) and 5%wt activated carbon fiber (the amount added is relative to the total mass of the CuMn metal oxide precursor and pseudo-boehmite) and mix them evenly. (Activated carbon fiber purchase manufacturer: Jiangsu Xinju Environmental Protection Technology Co., Ltd.; model: XJF-100; website: www.ahxj- acf.com . )
[0033] (3) After the raw materials are stirred evenly, a 10% (volume fraction) dilute nitric acid solution is added, and the raw materials are bonded into a mass according to a ratio of raw materials to dilute nitric acid water powder of 1.4:1, and aged at room temperature for 24 hours.
[0034] (4) The raw material is extruded into a mold and aged again at room temperature for 24 hours.
[0035] (5) Place the formed catalyst in an oven and dry at 100°C for 24 hours.
[0036] (6) The dried catalyst was placed in a muffle furnace and calcined at 500° C. for 3 hours to obtain a composite manganese-based catalyst.
[0037] Embodiment 2:
[0038] (1) Ce(NO3)3 and Mn(NO3)2 metal salts were dissolved in water at a metal element molar ratio of 1:3, 2 mol / L NaOH solution was added to the solution as a precipitant, and the solution was stirred until the pH value was 12; after 24 hours of static aging, the solution was filtered, washed, and dried at 100°C for 24 hours to obtain a CeMn metal hydroxide precursor.
[0039] (2) CeMn metal oxide precursor and pseudo-boehmite are added into a ball mill at a mass ratio of 7:3, and 3%wt talcum powder (the amount added is relative to the total mass of CeMn metal oxide precursor and pseudo-boehmite) and 5%wt activated carbon fiber (the amount added is relative to the total mass of CeMn metal oxide precursor and pseudo-boehmite) are added at the same time, and mixed evenly.
[0040] (3) After the raw materials are stirred evenly, a 10% volume fraction of dilute nitric acid solution is added, and the raw materials are bonded into a mass according to a ratio of raw materials to dilute nitric acid water powder of 1.2:1, and aged at room temperature for 24 hours.
[0041] (4) The raw material is extruded into a mold and aged again at room temperature for 24 hours.
[0042] (5) Place the formed catalyst in an oven and dry at 120°C for 24 hours.
[0043] (6) The dried catalyst was placed in a muffle furnace and calcined at 500° C. for 4 hours to obtain a composite manganese-based catalyst.
[0044] Embodiment 3:
[0045] (1) Dissolve two metal salts of Cu(NO3)2 and Mn(NO3)2 in water at a metal element molar ratio of 1:3, add 3 mol / L KOH solution as a precipitant, and stir the solution until the pH value is 12; after 24 hours of static aging, filter, wash, and dry at 100°C for 24 hours to obtain a CuMn metal hydroxide precursor.
[0046] (2) CuMn metal oxide precursor and pseudo-boehmite are added into a ball mill at a mass ratio of 7:3, and 2%wt sesbania gum (the amount added is relative to the total mass of the CuMn metal oxide precursor and pseudo-boehmite) and 1%wt activated carbon fiber (the amount added is relative to the total mass of the CuMn metal oxide precursor and pseudo-boehmite) are added at the same time, and mixed evenly.
[0047] (3) After the raw materials are stirred evenly, a 2.5% by volume dilute nitric acid solution is added, and the raw materials are bonded into a mass according to a ratio of raw materials to dilute nitric acid water powder of 1.3:1, and aged at room temperature for 24 hours.
[0048] (4) The raw material is extruded into a mold and aged again at room temperature for 24 hours.
[0049] (5) Place the formed catalyst in an oven and dry at 100°C for 24 hours.
[0050] (6) The dried catalyst was placed in a muffle furnace and calcined at 450° C. for 3 hours to obtain a composite manganese-based catalyst.
[0051] Embodiment 4:
[0052] (1) Two metal salts, Fe(NO3)3 and Mn(NO3)2, were dissolved in water at a metal element molar ratio of 1:3, 4 mol / L NaOH solution was added to the solution as a precipitant, and the solution was stirred until pH = 10; after 24 hours of static aging, the solution was filtered, washed, and dried at 120°C for 16 hours to obtain a FeMn metal hydroxide precursor.
[0053] (2) FeMn metal oxide precursor and pseudo-boehmite are added into a ball mill in a mass ratio of 9:1, and 5%wt talcum powder (the amount added is relative to the total mass of FeMn metal oxide precursor and pseudo-boehmite) and 5%wt activated carbon fiber (the amount added is relative to the total mass of FeMn metal oxide precursor and pseudo-boehmite) are added at the same time, and mixed evenly.
[0054] (3) After the raw materials are stirred evenly, a 15% volume fraction of dilute nitric acid solution is added, and the raw materials are bonded into a mass according to a ratio of raw materials to dilute nitric acid water powder of 1.1:1, and aged at room temperature for 24 hours.
[0055] (4) The raw material is extruded into a mold and aged again at room temperature for 48 hours.
[0056] (5) Place the formed catalyst in an oven and dry at 120°C for 24 hours.
[0057] (6) The dried catalyst was placed in a muffle furnace and calcined at 550° C. for 6 hours to obtain a composite manganese-based catalyst.
[0058] Comparative Example 1
[0059] (1) Preparation of catalyst
[0060] Except that activated carbon fiber was not added during the catalyst preparation process, other conditions were the same as those in Example 2;
[0061] (2) Catalytic performance test
[0062] Taking the degradation of ethyl acetate as an example, the degradation rate of the catalyst degradation curve after adding activated carbon fiber at each temperature was significantly improved compared with the catalyst without adding activated carbon fiber.
[0063] Comparative Example 2
[0064] (1) Preparation of catalyst
[0065] According to Example 2, after step (1), the catalyst was directly calcined in a muffle furnace at 500° C. for 4 hours to obtain a co-precipitated CeMn catalyst.
[0066] (2) Catalytic performance test
[0067] Taking the degradation of ethyl acetate as an example, the catalyst prepared by this patent has better performance in degrading ethyl acetate than the catalyst prepared by the ordinary co-precipitation method.
[0068] Figure 1 Comparison of the effects of degrading different VOCs in Example 1, reaction space velocity is 6000h -1 , the VOCs concentration is 1000ppm, among which the degradation rates of toluene, xylene, ethyl acetate and butyl acetate reach more than 98% at temperatures of approximately 180℃, 240℃, 100℃ and 180℃ respectively.
[0069] Figure 2 The comparison between Example 1 and Example 2 shows the catalytic degradation of ethyl acetate by the catalyst before and after adding 5% mass fraction of activated carbon fiber; the air velocity condition is 15000h -1 ; The ethyl acetate concentration is 1000ppm. After adding activated carbon fiber, the degradation rate of ethyl acetate is improved at all temperature points. The addition of activated carbon fiber is beneficial to the capture of low-concentration ethyl acetate in the air by the catalyst and improves the catalytic activity.
[0070] Figure 3 This is a comparison chart of the effects of Comparative Example 2 and Example 2, comparing the effects of the catalyst prepared by the general coprecipitation method and the catalyst prepared by Example 2 of this patent on the catalytic degradation of ethyl acetate; the space velocity condition is 15000h -1 ; The concentration of ethyl acetate is 1000ppm. The catalyst prepared by this patent can effectively improve the catalyst's ability to degrade ethyl acetate in a low temperature environment.
Claims
1. A method for preparing an activated carbon fiber composite manganese-based catalyst for catalytic combustion of VOCs, characterized in that: The following steps are involved: (1) adding a precipitant to a metal salt solution for precipitation, and then aging, filtering, washing and drying in sequence to obtain a metal hydroxide precursor; (2) adding a metal hydroxide precursor, a solid forming agent, an extrusion agent and activated carbon fibers into a ball mill, grinding and mixing them uniformly; after mixing, adding acid to make the raw materials bond into a mass and age; (3) extruding and aging the material after aging in step (2) again; (4) Drying the aged material in step (3), and then calcining it to obtain a composite manganese-based catalyst.
2. The method for preparing the activated carbon fiber composite manganese-based catalyst according to claim 1, characterized in that: In step (1), the metal composition in the metal salt is copper-manganese in a molar ratio of 1-3:1-3, iron-manganese in a molar ratio of 1-3:1-3, or cerium-manganese in a molar ratio of 1-3:1-3.
3. The method for preparing the activated carbon fiber composite manganese-based catalyst according to claim 1, characterized in that: In step (1), the precipitant is one of a sodium hydroxide solution or a potassium hydroxide solution, the concentration of the precipitant is 1 to 4 mol / L, and the precipitation condition is a pH value of 10 to 12.
4. The method for preparing the activated carbon fiber composite manganese-based catalyst according to claim 1, characterized in that: In step (1), the drying temperature is 60-120° C. and the drying time is 12 to 24 hours.
5. The method for preparing the activated carbon fiber composite manganese-based catalyst according to claim 1, characterized in that: In step (2), the solid forming agent is one of pseudo-boehmite or alumina, and the extruding agent is one of sesbania gum or talc.
6. The method for preparing the activated carbon fiber composite manganese-based catalyst according to claim 1 or 5, characterized in that: In step (2), the mass ratio of the solid forming agent to the metal hydroxide precursor is 3-7:3-10; the mass of the extrusion agent added is 2-5% of the total mass of the solid forming agent and the metal hydroxide precursor; and the amount of activated carbon fiber added is 1%-5% of the total mass of the solid forming agent and the metal hydroxide precursor.
7. The method for preparing the activated carbon fiber composite manganese-based catalyst according to claim 1, characterized in that: In step (2), the acid added is a nitric acid solution with a volume fraction of 2.5 to 15%; the volume ratio of the raw material to the acid after ball milling is 1:1 to 1.7:
1.
8. The method for preparing the activated carbon fiber composite manganese-based catalyst according to claim 1, characterized in that: In steps (1) to (3), the aging temperature is room temperature and the aging time is 24 to 48 hours. Preferably, in step (4), the drying temperature is 100-140° C., and the drying time is 20-24 hours; the calcination temperature is 450-550° C., and the calcination time is 3-6 hours.
9. An activated carbon fiber composite manganese-based catalyst for catalytic combustion of VOCs, characterized in that: The catalyst is prepared by the method described in any one of claims 1 to 8.
10. Use of the catalyst prepared by the method of claim 1 in catalytic combustion of VOCs.
Citation Information
Patent Citations
A catalyst for VOC catalytic combustion, its preparation method and application
CN114984942B
Mn-Ce catalyst for catalytic combustion of VOC waste gas
CN116712993A
Manganese peroxide loaded active carbon fiber for removing NOx at room temperature and preparation method thereof
CN103566928A
Composite carbon fiber-loaded metal catalyst as well as preparation method and application thereof
CN103915633A
Carbon fiber and metal oxide composite carrier metal catalyst and preparation method
CN106824202A